17β-Estradiol augments antidepressant efficacy of escitalopram in ovariectomized rats: Neuroprotective and serotonin reuptake transporter modulatory effects. (December 2016) - Ibrahim, Weam W.; Safar, Marwa M.; Khattab, Mahmoud M.; Agha, Azza M.
Highlights: Estrogen augmented escitalopram's effect in relieving menopausal depression. Estrogen's antidepressant effect was abolished by pretreatment with tamoxifen. Estrogen did not affect escitalopram-induced memory improvement. Estrogen potentiated escitalopram's effects on BDNF, SERT and TNF-α expressions. Estrogen did not alter escitalopram's effects on AchE, 5-HT1A or ERs expressions. Abstract: The prevalence or recurrence of depression is seriously increased in women during the transition to and after menopause. The chronic hypo-estrogenic state of menopause may reduce the response to antidepressants; however the influence of estrogen therapy on their efficacy is still controversial. This study aimed at investigating the effects of combining escitalopram with 17β-estradiol on depression and cognitive impairment induced by ovariectomy, an experimental model of human menopause. Young adult female Wistar rats were subjected to either sham operation or ovariectomy. Ovariectomized animals were treated chronically with escitalopram (10 mg/kg/day, i.p) alone or with four doses of 17β-estradiol (40 μg/kg, s.c) given prior to the behavioral tests. Co-administration of 17β-estradiol improved escitalopram-induced antidepressant effect in forced swimming test verified as more prominent decrease in the immobility time without opposing its memory enhancing effect in Morris water maze. 17β-estradiol augmented the modulatory effects of escitalopram on the hippocampal levels of brain-derived neurotrophic factor and serotonin reuptake transporter as well as tumor necrosis factor-alpha without altering its effects on the gene expressions of serotonin receptor 1A, estrogen receptors alpha and beta, or acetylcholinestearase content. This combined therapy afforded synergistic protective effects on the brain histopathological architecture, particularly, the hippocampus. The antidepressant effect of 17β-estradiol was abolished by pretreatment with estrogen receptor antagonist, tamoxifen (10 mg/kg, p.o). In conclusion, 17β-estradiol-induced antidepressant effect was confined to intracellular estrogen receptors activation. Moreover, 17β-estradiol enhanced escitalopram's efficiency in ameliorating menopausal-like depression, via exerting synergistic neuroprotective and serotonin reuptake transporter modulatory effects, without impeding escitalopram-mediated cognitive improvement.